Data modification attacks protection using blockchain signing and verification process in bluetooth low energy network / Aiman Nurrasyid Shahrul Kamil - Shahrul Kamil, Aiman Nurrasyid (2020)
Data integrity is a major concern in IoT technologies, and this issue has started to increase in recent years due to the use of Bluetooth Low Energy (BLE) devices. The unauthorized modification of confidential data is one the main threats and is commonly addressed by cryptographic mechanisms, through encryption. However, in BLE 4.2 environment, encryption algorithms are only applied between BLE devices and gateway thus leaving the network to be vulnerable on the public side of the BLE network which is between the gateway and the server. The vulnerabilities in BLE 4.2 and 5.x add an attractive perspective to the security of IoT technology. The issue of providing end-toend data protection should has been given highest priority by IoT application developer because the data in both private and public networks can be modified and disrupted by attacker. This research proposes some of the blockchain function which is signing and verification process on the BLE (Bluetooth Low Energy) network environment due the security issue on the BLE itself using three different hash algorithm MD5, SHA1 and SHA256. There are four experiment conducted such as processing time, power usage, memory usage and data modification attack. Based on the results, even though the proposed solution requires double hashing process it is still acceptable to be implemented due to it only require lower processing time and power/memory usage.